(untitled) (International Journal of Food and Nutritional Sciences, 2022)
A radio Lehmer-3 mean labeling of a connected graph G is a one to one map h from the vertex set V (G) to the set of natural numbers N such that for two distinct vertices x and y of G, d(x,y)+⌈(〖h(x)〗^3+〖h(y)〗^3)/(〖h(x)〗^2+〖h(y)〗^2 )⌉ ≥ 1 + diam(G). The radio Lehmer-3 mean numer of h, 〖rl〗_3mn (h) is the maximum number assigned to any vertex of G. The radio lehmer-3 mean number of G, 〖rl〗_3mn (G) is the minimum value of 〖rl〗_3mn (h) taken over all radio lehmer-3 mean labeling h of G. In this paper we investigateradio Lehmer-3 mean labeling of some graphs.